Exploring the anti-tumoral effects of tick saliva and derived components. (August 2015) - Sousa, Ana Carolina Prado; Szabó, Matias Pablo Juan; Oliveira, Carlo Jose Freire; Silva, Marcelo José Barbosa
Abstract: Ticks are blood-feeding arthropods with an outstanding ability to remain attached to its host for considerable periods while blood-feeding and remaining unnoticed. Their success results from the ability to modulate hemostatic and host immune responses. The ability to "bypass" a host's defenses, prevent blood clotting and wound healing makes ticks utterly interesting animals for the development of new drugs. Studies worldwide on various tick species have shown that tick saliva possesses a wide array of lipidic and proteic biomolecules with useful properties. These include not only immunomodulatory, anti-inflammatory, anti-platelet and anti-clotting properties, but also cytotoxic and cytolitic properties that act against various cell types, and anti-angiogenic properties, which have gained increasing prominence. We searched PubMed, Science Direct, Elsevier and other sites for publications regarding tick saliva and its effects on cancer cells and angiogenesis. Our aim was to compile a list of molecules with potential for host adaptation and for the development of new cancer treatment drugs.